Oncology practitioners' perspectives and practice patterns of post-treatment cancer survivorship care in the Asia-Pacific region: Results from the STEP study - Raymond Javan Chan (2018)
© 2017 The Author(s). Background: Most efforts to advance cancer survivorship care have occurred in Western countries. There has been limited research towards gaining a comprehensive understanding of survivorship care provision in the Asia-Pacific region. This study aimed to establish the perceptions of responsibility, confidence, and frequency of survivorship care practices of oncology practitioners and examine their perspectives on factors that impede quality survivorship care. Methods: A cross-sectional survey of hospital-based oncology practitioners in 10 Asia-Pacific countries was undertaken between May 2015-October 2016. The participating countries included Australia, Hong Kong, China, Japan, South Korea, Thailand, Singapore, India, Myanmar, and The Philippines. The survey was administered using paper-based or online questionnaires via specialist cancer care settings, educational meetings, and professional organisations. Results: In total, 1501 oncology practitioners participated in the study. When comparing the subscales of responsibility perception, frequency and confidence, Australian practitioners had significantly higher ratings than practitioners in Hong Kong, Japan, Thailand, and Singapore (all p < 0.05). Surprisingly, practitioners working in Low- and Mid- Income Countries (LMICs) had higher levels of responsibility perception, confidence and frequencies of delivering survivorship care than those working in High-Income Countries (HICs) (p < 0.001), except for the responsibility perception of care coordination where no difference in scores was observed (p = 0.83). Physicians were more confident in delivering most of the survivorship care interventions compared to nurses and allied-health professionals. Perceived barriers to survivorship care were similar across the HICs and LMICs, with the most highly rated items for all practitioners being lack of time, dedicated educational resources for patients and family members, and evidence-based practice guidelines informing survivorship care. Conclusions: Different survivorship practices have been observed between HICs and LMICs, Australia and other countries and between the professional disciplines. Future service planning and research efforts should take these findings into account and overcome barriers identified in this study.